Post-war French writings on Black Africa - Yillah, D; Yillah, Dauda (2007)
﻿ Edward Said stresses the politically and ideologically skewed nature of western imperial responses to colonised or formerly colonised cultures and peoples, articulated in a variety of media, including scholarly and imaginative writings, which are inflected by the various kinds of power (political, intellectual, cultural and moral) that the West has wielded and continues to wield over non-Western regions of the world. While recognising the pathbreaking import of Said's work, critics have pointed out his blindness to the possibilities of resistance to and subversion of the discourse of Empire within the western-authored texts that he discusses. Even where he does consider the issue of resistance and opposition to Empire by western intellectuals, he still stresses the complicity of their texts with the processes of Empire. If one were to pursue the logic of such criticisms to its limit and apply it to the intellectual resistance generated from the centre in the context of the post-War dismantling of European overseas empires and its aftermath, one might be tempted to conclude that such resistance constitutes an unqualified disruption of colonial modes of apprehending difference. Against the backdrop of such readings of Said, this thesis examines the issue of cross-cultural representation in a selection of mainstream metropolitan French writings relating to black Africa produced between 1945 and the present. It brings together scholars and writers like Gide, Sartre and Griaule, some of whose works relating to black Africa belong to the first decade of the post-War period marked by France's continued colonial presence in the continent. It also considers other scholars and writers like Dumont, Conchon, Verchave and Le Clézio, whose books appeared in the second and succeeding decades of the period. The overall aim is to identify the ways in which these writers respond individually and collectively to black Africa often construed as a paradigm of cultural difference, and to consider whether such cross-cultural responses, given their historical context, can be described as being invariably a function of the changing relations between France and black Africa. What forms do the cross-cultural responses take? What cultural assumptions and ideological motivations shape those responses? Are the responses entirely disruptive of colonial modes of relating to difference? If not, what are their aporias, their ambiguities and paradoxes? My conclusion is that while Sartre and others relate to black Africa with unmistakeable empathy, their positive cross-cultural disposition does not necessarily enable them to attain a relationship with the peoples and cultures of Africa which is an equipollent relationship between equals.